Chromium, Cadmium, and Lead Dynamics During Winter Foliar Litter Decomposition in an Alpine Forest River. Issue 1 (1st February 2016) - Yue, Kai; Yang, Wanqin; Peng, Yan; Zhang, Chuan; Huang, Chunping; Wu, Fuzhong
ABSTRACT: Little information is currently available about heavy metal dynamics during litter decomposition in areas receiving few inputs of exotic metals. A field litter decomposition experiment was conducted during the winter in an alpine forest river on the eastern Tibetan Plateau. Concentrations, release rates, and release rate per day of chromium (Cr), cadmium (Cd), and lead (Pb) were investigated in the foliar litter of willow ( Salix paraplesia ), azalea ( Rhododendron lapponicum ), cypress ( Sabina saltuaria ), and larch ( Larix mastersiana ) during the prefreezing, freezing, and thawing periods. Concentrations of Cr in willow, cypress, and larch; Cd in all foliar litter types; and Pb in azalea foliar litter increased following incubation over an entire winter. Both Cr and Pb showed patterns of accumulation during the prefreezing period and patterns of release in the freezing and thawing periods, but Cd showed accumulation in all three periods. Water temperature, pH, flow velocity, conductivity, and nutrient availability in the river were significantly related to the dynamics of these heavy metals in the decomposing foliar litter. The heavy metal accumulation pattern in running water suggested an absolute increase in metal mass, indicating that litter may act as an efficient metal "cleaner" and contribute to an ecosystem's capacity for self-purification.